Retrospective and statistical analysis of hand and forearm injuries in the Silesian pediatric population - study of post-traumatic X-rays in 2022. - Magdalena Machnikowska-Sokołowska; Marcin Ciekalski; Iga Szymańska; Jakub Mordarski; Katarzyna Gruszczyńska (PLoS ONE)
Background and objectives Upper limb injuries are a common occurrence in the pediatric demographic, particularly wrist injuries, which constitute a noteworthy subset. Fractures involving the forearm, wrist, and phalanges are recurrent reasons prompting visits to emergency departments. This investigation endeavors to offer a comprehensive insight into hand and forearm fractures within the pediatric cohort, delineating data across various age groups, gender distributions, and fracture location. Materials and methods This study involved data from the reports of 834 post-traumatic wrist X-ray examinations conducted in 2022 at the Department of Diagnostic Imaging of the Upper Silesian Child Health Centre. The analysis included bone injuries, the age and gender of the child, the nature of the lesions, and anatomical location of the injury. The study group consisted of 327 girls and 511 boys, who were on average 11.4 ±  3.6 and 12.0 ±  3.8 years old, respectively. Results There were 273 single fractures and 66 multiple fractures in the study group. The highest number of fractures were recorded in the metacarpal bones (29,2%), among which the fifth meta-carpal bone was the most frequently injured (14,5%). The second most common fracture was in the forearm (28,9%). There were 55 phalangeal fractures in the study group (16,2%). Conclusions The risk of fractures is statistically highest among boys, peaking at 12 years of age. The metacarpal bones and the radius are most susceptible to fractures. The likelihood of fractures in the right and left hand is similar in females, whereas males are more likely to sustain injuries to the right hand.